Macroeconomic policies and agricultural and rural development - Díaz-Bonilla, Eugenio (Food and Agriculture Organization of the United Nations, 2019)
This chapter briefly discusses different aspects of macroeconomic policies and its interactions with agriculture, rural development and food security in Latin America and the Caribbean. It attempts to summarize some relevant topics that policymakers and policy analysts working on agricultural issues in developing countries should understand about macroeconomics to do their job. It considers the impact of macroeconomic conditions and policies on agriculture, but also the influence of agricultural events on the general economy.